Formation of foreign language competence in students of economic specialities - Matiychak, Aliona; Muradkhanian, Iryna; Cherska, Zhanna (Науковий вісник Міжнародного гуманітарного університету, 2019)
The purpose of the article is to investigate the mechanisms of forming foreign language competence in students of economics in the frameworks of Business English and German for Business courses on the basis of modern vocabulary and a series of vocabulary and communication exercises, which should result in oral and written communication on the professional level. In such a way we try to reinforce the students’ grammar skills working on contextual examples and practice exercises. It is of utmost importance that the information of both the general professional field and narrowly specialized aspects be trained comprehensively in reading, listening, writing and speaking, which creates favorable prerequisites for forming thecommunicative competence of specialists in economy and future businessmen. So, in particular, one and the same theme is optimally revealed, in our opinion, on authentic professional material. The topics of the course include such generally professional aspects as: company structure; career choices and finding a job; preparing a resume; job interview; e-mail etiquette; e-commerce; internet sales; telephoning; ordering, and checking information; complaining; writing memos, completing order forms; creating marketing plans and conducting meetings; effective advertising techniques; presenting products; banking and accounting; dealing with bank accounts and credit cards; corporate culture etc. The analysis shows that the model of “listening, reading, writing, speaking” is the most acceptable for successful business communication. The result of using such a mechanism is the development of communicative competence of future specialists, who are able to understand the interlocutor and to respond not only at everyday, but also on the modern professional level, be able to reproduce and find relevant information and communicate on business in writing.
Keywords: competence; reading; listening; writing; speaking; business